IMF Staff papers : Volume 41 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1994)
Primary commodities still account for the bulk of exports in many developing countries. However, real commodity prices have been declining almost continuously since the early 1980s. The appropriate policy response to a terms of trade shock depends importantly on whether the shock is perceived to be temporary or permanent. Our results indicate that the recent weakness in commodity prices is mostly secular, stressing the need for commodity exporting countries to concentrate on export diversification and other structural policies. There is, however, scope for stabilization funds and the use of hedging strategies, since the evidence also suggests commodity prices have become more volatile.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet